2010
DOI: 10.1139/w10-033
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of integron-linked antibiotic resistance genes in strains ofSalmonellaspp. isolated from swine in Chile in 2005 and 2008

Abstract: Salmonella spp. isolates obtained from healthy swine in 2008 were analyzed for antibiotic resistance phenotypes and genotypes. The resistance profiles of the 2008 isolates were compared with those of a Salmonella collection isolated from the same geographical area in 2005. The 2008 isolates consisted of strains that were 97% oxytetracycline resistant, 33.3% amoxicillin resistant, 31.8% amoxicillin- plus clavulanic acid resistant, 27.5% trimethoprim-sulfamethoxazole resistant, 17.3% streptomycin resistant, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
1
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 26 publications
1
5
1
2
Order By: Relevance
“…In this study, we used the PCR method to determined the occurrence of class 2 integrons and associated gene cassettes (aadA1, sat2 and dfrA1) in Tn7-like-positive isolates. Similar gene cassettes (aadA1, sat2, and dfrA1)have been obtained in the most of animals-derived Enterobacteriaceae isolates (46,47).The presence of the gene cassette and its corresponding phenotypic resistance was matched (Tables 2 and 3). This explains why Tn7-like bacteria are highly resistant to Trimethoprim/Sulfamethoxazole and Streptomycin, and may pose the risk of widespread dissemination of large, single assemblage repositories of resistance genes and threatening the emergence of a postantibiotic era (48).…”
Section: Discussionsupporting
confidence: 68%
“…In this study, we used the PCR method to determined the occurrence of class 2 integrons and associated gene cassettes (aadA1, sat2 and dfrA1) in Tn7-like-positive isolates. Similar gene cassettes (aadA1, sat2, and dfrA1)have been obtained in the most of animals-derived Enterobacteriaceae isolates (46,47).The presence of the gene cassette and its corresponding phenotypic resistance was matched (Tables 2 and 3). This explains why Tn7-like bacteria are highly resistant to Trimethoprim/Sulfamethoxazole and Streptomycin, and may pose the risk of widespread dissemination of large, single assemblage repositories of resistance genes and threatening the emergence of a postantibiotic era (48).…”
Section: Discussionsupporting
confidence: 68%
“…But to the best of our knowledge, three gene cassette arrays, aac(6')-Ib-cr-aar-3-dfrA27-aadA16, aacA4-catB3-dfrA1 and aadA2-lnuF (Table 3), are reported for the first time in surface water. It is interesting to find that the gene cassettes inserted in the class 1 and 2 integrons carried by E. coli isolated from the Dongjiang River are similar to those found in E. coli isolated from poultry (Soufi et al, 2009;Vasilakopoulou et al, 2009), swine (Lapierre et al, 2010), and human (Vasilakopoulou et al, 2009). The high similarity of class 1 and 2 integrons gene cassettes among E. coli isolated from clinical specimens, poultry, swine, and river water strongly indicates that surface water plays a key role in spreading ARGs in the environment, which originate from animal and human sources.…”
Section: Discussionmentioning
confidence: 89%
“…The aadA22, dfrA17-aadA5, and dfrA12-aadA2 cassette arrays were commonly found in isolates from all samples. These three cassette arrays have been found frequently in Enterobacteriaceae isolates from animal and environmental samples (4,20,46,58), which suggests that class 1 integrons carrying gene cassettes play an important role in conferring resistance to trimetho prim and aminoglycoside among our MDR Enterobacteria ceae strains. Conjugation experiments revealed that some class 1 integrons carrying the dfiA12-aadA2, dfrAl-aadAl, or aadB-orfl-cmlA gene cassette array could horizontally transfer to E. coli, suggesting that these integrons are located on transmissible plasmids.…”
Section: Discussionmentioning
confidence: 99%